Light limitation helps stabilize the phytoplankton assemblage steady-state in a temperate and highly turbid, hypertrophic shallow lake (Laguna Chascomús, Argentina) - Iachetti, Clara Margarita (2014)
We performed a 30-month field study in a highly turbid, hypertrophic shallow lake from the Pampa Plain (Argentina) in order to investigate the occurrence of steady-state phases of phytoplankton, with an emphasis on the effect of subtle, but measurable, increase in light availability. The results revealed that a steady-state condition prevailed during the first 14 months, during which Aphanocapsa cf. delicatissima represented, on average, 91% of the total phytoplankton biomass. The statistical analyses provide support for the hypothesis that low light availability in the water column regulates the structure of the algal assemblage in this lake. Our results agree with predictions of the light-limited growth theory (i.e. the observed increase in light supply promoted an increase in algal density) and are also consistent with the notion that environmental constraints influence the dominant morphological traits in phytoplankton assemblages, particularly, that small organisms and/or attenuated forms are favoured under very poor light conditions. Nevertheless, further work is needed to get a full understanding of the processes controlling phytoplankton dynamics in this lake, including careful studies of the ecophysiology of the colonies comprising pico-sized cells of Aphanocapsa cf. delicatissima that dominated the assemblage during all the studied period.